Planning Strategy Spatial Plan for the Province of Central Kalimantan - Rahmawati Rahmawati; Tjahya Supriatna; Sampara Lukman; Dahyar Daraba (Budapest International Research and Critics University, 2021)
The background of this research is that since the stipulation of Regional Regulation Number 5 of 2015 concerning the RTRW of Central Kalimantan Province until now the implementation has not been as expected, this can be seen through the problems that occur starting from the determination of the area into an office area, settlement and for investment purposes in the construction stage in the forest area. Meanwhile, the purpose of this study is to analyze and find out the RTRW planning for Central Kalimantan Province which has not yet been optimally implemented, analyze and find out the inhibiting factors for Central Kalimantan Provincial RTRW planning and formulate the Central Kalimantan Provincial RTRW planning strategy. The focus of this research is to analyze the RTRW planning strategy of Central Kalimantan Province, and to formulate the RTRW planning strategy used by Central Kalimantan Province. This research uses qualitative research with descriptive method. The results show that there are two things that affect the regional spatial planning process, namely First, micro factors related to development both from the manager's point of view and from the provider's point of view, including technical, managerial management), Financial (finance), Economics, Environmental impact, Social and security. Second, macro factors, namely the government's problem to see the relationship between projects and government programs as a whole, which consists of the suitability of the location and regional economic development strategies. Third, Central Kalimantan the provincial RTRW planning strategy uses ASOCA's Internal and External Factors Strategy Analysis which results in other Agility to produce a more optimal RTRW planning strategy through the ASC Rahma Strategy. ASC Rahma's strategy is through a synoptic planning approach which consists of the first synoptic planning, procurement of forest areas based on the outline of regional needs, the second synoptic planning, encouraging RDTR to be immediately established as an operational implementation of investment activities on a micro scale, the third synoptic planning, supervising preparation of the RTRW so that it can be accepted by the community. All stakeholders, and the fourth synoptic planner, ensures that the RTRW planning does not experience difficulties in its implementation in the field.